A VISION OF UNITY : SELECTED WRITINGS ON HISTORY, POLITICS, PHILOSOPHY AND LITERATURE - S.M.Y. Kayseri (Petaling Jaya, Selangor : Penerbitan Cakna, 2025)
A Vision of Unity: Selected Writings on History, Politics, Philosophy and Literature is a journey through the timeless search for harmony, weaving insights from history, philosophy, psychology, and literature into a single tapestry. The first part, Civitas, explores how major thinkers$1 (Bfrom Samuel P. Huntington and Francis Fukuyama to Thomas Sowell$1 (Benvisioned unity amid the shifting currents of politics and history. Here, the author introduces his unique idea of concord: the natural tendency of diverse groups to come together into a united whole, not through assimilation or force, but through shared lived experiences$1 (Ba dynamic he calls spectations. The second part, Noesis, ventures into the philosophical landscapes of Spinoza$1 (Bs rationalism, Kant$1 (Bs transcendental idealism, and Hussert$1 (Bs phenomenology. it traces how the eternal quest in study of lived experience by Western philosophers made complete by the intuitive insights of Islamic metaphysics, offering a profound vision of the intuition of Being. The third part, Mythos, calls for a return to humanity$1 (Bs mythopoetic imagination$1 (Bthe deep symbolic understanding of life that flourished before the Enlightenment$1 (Bs age of reason. it reminds us of a time when destiny, belonging, and Reality itself were intimately woven into everyday existence.s
Bibliography: page [305-309]
Keywords: Philosophy; Unity (Philosophy); Political philosophy; Civilization -- Philosophy